Mathematics
namathai
11

Solving systems of equations by elimination -4x+9y=9 X-3y=-6

+1
(1) Answers
envadina

Manipulate the equations until one of the variables match up I'm going to cancel the y-values. -4x+9y=9 x-3y=-6 the way to do that is to multiply all the numbers, on both sides of the equation, by 3. 3(x-3y)=3(-6) 3x-9y=-18 Now that the y value matches up with the other one, add the 2 equations  -4x+9y=9 + 3x-9y=-18 The resulting equation is -x=-9, so x=9. Plug this new x-value into one of the original equations to find the y-value. x-3y=-6 (9)-3y=-6 -3y=-15, so y=5 Check your work by plugging the 2 variables into both equations and the results should both be true. -4(9)+9(5)=9       -36+45=9     9=9 (9)-3(5)=-6     9-15=-6     -6=-6 So y=5 and x=9

Add answer